THE EVALUATION OF INFORMATION SYSTEM IN PT. JATIDIRI TRANS BASED ON DELONE AND MCLEAN IS SUCCESS MODEL (Journal of Business and Management, 2021)
Ever since the Covid-19 pandemic began in 2019, the demand of import and the supply of export decreases and it affect the performance of the freight forwarding industry. The pandemic also accustoms people to limit physical interactions with the use of technology and the acceleration of information exchange. Hence to adapt with the current situation, companies must optimize their information system through evaluations. Therefore, this research is conducted to evaluate the information system of PT. Jatidiri Trans located in Jakarta, according to the perspective of users based on the DeLone and McLean Information system Success Model (D&M Model) (2003). The data collection of the research was obtained through a five likert questionnaire (5 indicates strongly agree and 1 indicates strongly disagree) which contains of six interrelated IS success variables; System Quality, Information Quality, Service Quality, Use, User Satisfaction, and Net Impact. The data were distributed to 24 users of the information system. The relationship of the obtained data was analyzed by using Partial Least Square Structural Equation Modelling (PLS-SEM). The output of this research validates the D&M model based on four significant hypotheses, namely Information Quality affects Use, Service Quality affects User Satisfaction, Use affects Net Impact, and User Satisfaction affects the Net Impact.Keywords: Information System Evaluation, PLS-SEM, IS Success Model